The efficacy of maintenance therapy after remission induction with tacrolimus in ulcerative colitis with and without previous tumor necrosis factor‐α inhibitor - Suzuki, Taketo (JGH Open, 2019)
BACKGROUND AND AIM: Tacrolimus (TAC) is an important therapeutic option for remission induction in patients with refractory ulcerative colitis (UC). However, there is little evidence available on long‐term outcomes and maintenance treatments after TAC therapy, especially in cases with previous tumor necrosis factor‐α (TNF‐α) inhibitor therapy. METHODS: Long‐term outcomes and remission induction after TAC treatment were retrospectively examined in refractory UC patients with and without previous TNF‐α inhibitor therapy. RESULTS: The mean disease activity index and the endoscopic activity index scores decreased significantly during the 12‐week treatment after TAC therapy in both groups, showing a significantly greater decrease in the group without TNF‐α inhibitor therapy than in the group with previous TNF‐α inhibitor therapy. One year or more after TAC therapy, TNF‐α inhibitor and/or azathioprine was used as maintenance therapy in most cases in the group without previous TNF‐α inhibitor treatment, while azathioprine was primarily used in the group with previous TNF‐α inhibitor treatment. Colectomy was performed in 45.5% (5/11) and 15.6% (7/45) of the groups with and without previous TNF‐α inhibitor therapy, respectively, and the group without previous TNF‐α inhibitor treatment had a better colectomy‐free rate than the group with previous TNF‐α inhibitor treatment after TAC therapy on Kaplan–Meier analysis. CONCLUSIONS: TAC is effective for remission induction in refractory UC patients with and without previous TNF‐α inhibitor treatment. Maintenance medication after TAC therapy is an issue for the future, especially in UC cases with previous TNF‐α inhibitor treatment failure.